2012
DOI: 10.1364/ol.37.000545
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon polariton compression through radially and linearly polarized source

Abstract: We report on the possibility of realizing a radial mode on a metallic conical structure by means of a linearly polarized incident wave. This result is utilized for observing surface plasmon polaritons adiabatic compression on a tapered conical nanostructure. The ingredients for radial mode generation are described in terms of phase-matching of the components of the electromagnetic field. We conclude by showing the robustness of this approach, explaining the polaritonic behavior as a function of the device geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
(25 reference statements)
2
33
0
Order By: Relevance
“…It sustains the propagation of electromagnetic field as SPPs till the apex, either in lossy [38,39] or in adiabatic mode [40,41]. The propagation along conical structures has been widely studied in literature [42,43]. Specifically, a conical plasmonic waveguide efficiently propagates radial modes [43][44][45][46], i.e.…”
Section: Metallic Cones and Plasmon Couplingmentioning
confidence: 99%
“…It sustains the propagation of electromagnetic field as SPPs till the apex, either in lossy [38,39] or in adiabatic mode [40,41]. The propagation along conical structures has been widely studied in literature [42,43]. Specifically, a conical plasmonic waveguide efficiently propagates radial modes [43][44][45][46], i.e.…”
Section: Metallic Cones and Plasmon Couplingmentioning
confidence: 99%
“…In fact it has been shown that a TM0 mode within the structure is needed in order to obtain the phenomenon [12][13][14]. This means that the propagating plasmon needs a particular symmetry in order to be squeezed along a tapered structure.…”
Section: The Adiabatic Compressionmentioning
confidence: 99%
“…Figure 1: a) Electric field in the x direction for a SP propagating in a conical structure. The anti-phase (AP) configuration enables a TM0 mode satisfying the requirements for the adiabatic compression [12]. b) Dependence of the real part of the effective refractive index on the radius value of a metallic cylinder [5].…”
Section: The Adiabatic Compressionmentioning
confidence: 99%
See 2 more Smart Citations